2011
DOI: 10.1038/onc.2010.637
|View full text |Cite
|
Sign up to set email alerts
|

α-Catulin knockdown induces senescence in cancer cells

Abstract: Cellular senescence functions as a tumor suppressor that protects against cancer progression. a-Catulin, an a-catenin-related protein, is reported to have tumorigenic potential because it regulates the nuclear factor-jB (NF-jB) pathway, but little is known about its clinical relevance and the mechanism through which it regulates cancer progression. Here, we found that a-catulin mRNA levels were significantly upregulated in cancer cell lines and clinical oral squamous cell carcinomas, which positively correlate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…We have found that silencing a-catulin in cancer cells decreased cell proliferation in vitro and in vivo (10). In this study, although a-catulin overexpression did not alter the cell proliferation rate, it promoted tumor growth in vivo (Supplementary Figs.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…We have found that silencing a-catulin in cancer cells decreased cell proliferation in vitro and in vivo (10). In this study, although a-catulin overexpression did not alter the cell proliferation rate, it promoted tumor growth in vivo (Supplementary Figs.…”
Section: Discussionmentioning
confidence: 56%
“…Inhibiting a-catulin, ILK, NF-kB, or integrin a V b 3 prevented cancer cell migration and invasion. In addition, a-catulin is known to have oncogenic potential through its interaction with IKK-b and induction of NF-kB activity (9) and by preventing cellular senescence (10). Moreover, inhibitors of ILK (27), NF-kB (45), and integrin (46) have been used in animal model studies and clinical trials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To address previous findings (26) that α-catulin-deficient cells are more apoptotic, we analyzed control and α-catulin-deficient human SCC cells for AnnexinV activity under normal culture conditions and after the induction of apoptosis (Supplementary Fig. S3B).…”
Section: Resultsmentioning
confidence: 99%
“…Notably, the majority of colon cancers have mutations in APC leading to protein truncation (Fodde et al, 2001b;Kinzler and Vogelstein, 1996;Smith et al, 1993), and deletion of APC in crypt stem cells in mice leads to transformation within days (Barker et al, 2009). α-Catulin (also known as CTNNAL1), a vinculin-related protein with homology to α-catenin, has also been shown to increase γH2AX levels when knocked down and may regulate cell fate (Fan et al, 2011). Taken together, these studies suggest the WNT pathway may be an important regulator of how the cell responds to DNA damage, and the mechanisms that regulate catenin activity in the cytoplasm may be conserved in the nucleus.…”
Section: Discussionmentioning
confidence: 99%